DESKRIPSI SIFAT FISIKO KIMIA BUAH BUNI (ANTIDESMA BUNIUS L. SPRENG) ASAL PULAU TIMOR - Gemma G. O. Laga; Herianus J. D. Lale; Zainal Abidin; Yuliana Tandi Rubak (Universitas Muhammadiyah Semarang, 2023)
The plant of Buni (Antidesma bunius L. Preng) has a relatively high value for use; however, its presence in Timor Island does not have sufficient notice from people around. In order to optimize its utilization and thus increase people’s recognition of it as well as to conserve the plant, a study has been conducted to record the physicochemical properties of the fruit as the starting step. The physical properties of the fruit studied are mainly the size and weight of the fruit, while the fruit chemical properties studied are proximate value, sugar content, vitamin C content, and total phenolic compounds. The fully ripe Buni fruits were collected from the Amarasi forest area, Kupang District. On average, the bignay fruit of Timor found 18 fruits per branch with a diameter of 6.69 mm, 3 g weight, and 62.44% edible proportion. The water content of the ripe fruit is 81.54% with vitamin C as the major nutrient of the fruit accounting for 20 mg/100 g of fruit, and total polyphenols content is quite high that reaching 459.18 mg GAE/100 g of the fruit.